A comparison of seasonal variations in rotavirus antibodies in the breast milk of Swedish and Bangladeshi mothers. (17th November 2014) - Novak, Daniel; Svennerholm, Ann‐Mari
Abstract Aim The rotavirus has been identified as the most common cause of severe gastroenteritis in young children. This study compared the levels of rotavirus‐specific antibodies in breast milk and serum samples in Swedish and Bangladeshi mothers to identify any seasonal variations. Methods Breast milk and serum samples were collected from 69 Swedish and 52 Bangladeshi mothers during all months of the year. Sera were analysed for Immunoglobulin A (IgA) and Immunoglobulin G (IgG) titres and breast milk for secretory IgA (SIgA) antibody levels against rotavirus. Results Significantly, higher SIgA antibody levels against rotavirus were found in breast milk from Bangladeshi than Swedish mothers (p < 0.0001). Seasonality of rotavirus antibody levels was only detected in breast milk from Swedish mothers, with samples collected during the spring having significantly higher rotavirus titres than samples collected during the autumn (p = 0.0203). Conclusion This study found significantly higher SIgA antibody levels against rotavirus in breast milk from Bangladeshi than Swedish mothers, together with a seasonal variation among Swedish mothers only. These results suggest that Swedish children who are being breastfed should ideally be vaccinated during seasons when the rotavirus antibody levels in breast milk are low.